Association of Proton Pump Inhibitor and Infection and Major Adverse Clinical Events in Patients With ST-Elevation Myocardial Infarction: A Propensity Score Matching Analysis - Liu, Yuan-Hui; Cao, Zhi-Yuan; Dai, Yi-Ning; Zeng, Li-Huan; Zhang, Ye-Shen; Fan, Hua-Lin; Duan, Chong-Yang; Tan, Ning; He, Peng-Cheng (Frontiers in Medicine, 2022)
Background: Infections are not common but important in patients with acute myocardial infarction, and are associated with worse outcomes. Infection was proved to be associated with the use of proton pump inhibitor (PPI) in several cohorts. It remains unclear whether PPI usage affects infection in patients with acute myocardial infarction. Methods: We consecutively enrolled patients with ST-elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) from January 2010 to June 2018. All patients were divided into the PPI group and non-PPI group according to whether the PPI was used. The primary endpoint was the development of infection during hospitalization. Results: 3027 patients were finally enrolled, with a mean age of 62.2 ± 12.6 years. 310 (10.2%) patients were developed infection during hospitalization. Baseline characteristics were similar between the PPI and non-PPI groups (n=584 for each group) after propensity score analysis. PPI usage was significantly associated with infection based on the propensity score matching analysis (adjusted OR = 1.62, 95% CI = 1.02-2.57, P = 0.041). Comparing to patients with non-PPI usage, PPI administration was positively associated with higher risk of in-hospital all-cause mortality (adjusted OR = 3.25, 95% CI = 1.06-9.97, P = 0.039) and in-hospital major adverse clinical events (adjusted OR = 3.71, 95% CI = 1.61-8.56, P = 0.002). Subgroup analysis demonstrated that the impact of PPI on infection was not significantly different among patients with or without diabetes and patients with age ≥ 65 years or age < 65 years. Conclusion: PPI usage was related to a higher incidence of infection during hospitalization, in-hospital all-cause mortality, and in-hospital MACE in STEMI patients.